Variáveis socioeconômicas e desenvolvimento de habilidades de controle inibitório: uma investigação com crianças de escola rural e urbana - Freitas, Lais Lopes de [UNIFESP] (2016)
Executive Functions (EF) are cognitive skills that influence academic and social performance. Among them, there is the Inhibitory Control (IC), an ability that allows the inhibition of automatic or preponderant behavior. There is an increasing scientific interest in understanding how these skills are expressed in the first years of schooling and the influence of socioeconomic variables on their development. The present study aimed to investigate the relations between IC skills and socioeconomic variables on the performance of children in the first years of elementary school in IC and other EF tasks as well as on emotional regulatory measures. A sample of 99 6 to 8 year olds children, of both sexes, from three different groups according to the region where they live and study (rural e urban areas from Brazópolis, and urban areas from Itajubá ? Minas Gerais) participated in the study. Cognitive aspects of IC were investigated by means of the Animals Stoop task and the Inhibition test from Nepsy-II, and behavioral aspects by means of the Emotional Regulation Inventory. Socioeconomic conditions were analyzed by means of inventories of family environmental and school resources, among others. Descriptive, inferential, correlational and regression statistical analyzes were executed. Results showed an age effect on speed of performance on IC tasks but not on number of errors. Children from rural zone were faster than the remaining in some of the measures. Those from Itajubá city made more errors. Quality of parental support and interaction were correlated to IC performance in only one of the groups; no significant correlations were identified between family resources and children emotional regulation skills, independently of region. These findings indicate that IC development in the first years of formal education is expressed mainly in terms of speed of tasks performance, and that some socioeconomic variables may influence in part this development.